FOREIGN EXPERIENCE IN THE DEVELOPMENT OF ECOLOGICAL AND ECONOMIC POTENTIAL OF THE APC (ON THE EXAMPLE OF THE USA) - SHKVARUK, Dina (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article explores the key aspects that have contributed to the success of the United States in creating a sustainable and efficient agricultural system, focusing on environmental and economic aspects. The role of the state in supporting the sustainable development of the agro-industrial complex is defined, pointing out the importance of proper regulation and stimulation of the sector. It is emphasized that the United States has successfully used economic incentives, such as financial incentives, tax incentives, and regulatory mechanisms to promote the development of the environmental and economic potential of the agro-industrial complex. The author also draws attention to the importance of partnerships between government agencies, industries, and the public sector in achieving sustainable development. It is shown that the United States actively engages scientific institutions, business environment and non-profit organizations to jointly develop innovative solutions and technologies aimed at preserving the environment and increasing the productivity of the agro-industrial complex. The level of US GDP and its importance in the formation of an efficient economy are characterized. The main characteristics of the development of the ecologically based economy in the country and innovative approaches and technologies, such as agricultural biotechnology, precision agriculture, water storage systems and energy efficiency, which contribute to increased productivity and reduced resource use, are outlined. In addition, the article notes that the success of the United States lies in a developed research and development system that promotes continuous innovation and adaptation to changing conditions. The article emphasizes the importance of taking into account environmental factors in the development of the agricultural sector, which can lead to increased production efficiency, reduced negative environmental impact and improved product quality. The results of the US study show that environmentally oriented approaches and innovative technologies can contribute to increased efficiency and sustainability in the agricultural sector.